Laser-Scatter Analysis of Micro Particles in Carbon Quantum Dot Suspensions Using Droplet Ball-Lenses (Patan Pragya, 2025)
Laser assisted optical microscopy of the carbon quantum dot (CQD) droplets is a new type tool to image micro- and nano-size structures in high resolution. The ball-lens method from which we sensed the size of objects that were encapsulated inside a hemispherical CQD droplet was also used for characterizing optical functionality of the CQD droplets as micro-lenses and their performance to detect particles at microscopic scale in suspended nano particles. Green light at 532 nm was focused by hemispherical CQD droplets (diameter 0.003 m) and magnified images were generated on a screened positioned 0.74 m away. The results of FTIR and XRD analyses corroborated the heterogeneous nature of CQDs that contain oxygenated, nitrogenated and aromatic domains resulting strong photo stability and optical responsiveness. The average image size of the 17 measurements is 0.01756 m in diameter, which corresponds to an estimated object size of about 75.310-6 m; optical features such as these most probably correspond to clusters of CQDs or residual impurities rather than individual nano particles and suggest that our approach may be sensitive to micro-scale entities. The limitation is that it cannot distinguish individual quantum dots, and nonspecific droplet-induced distortions can lead to aberrations. The innovation for our method is the facile and low-cost implementation of CQD droplets as micro impurity magnifying glasses, which provides valuable perspectives in material characterization and quality control.